Attitudes Of Parents And Behaviour Problems Of Children With Intellectual Disability (Journal of Pharmaceutical Negative Results, 2022)
Present study attempts to to explore the impact of parent's attitude towards disability on the behaviour problems of children with intellectual disability. The sample consisted of 50 parents of children with intellectual disability (N = 50). Data was individually collected from two major rehabilitation institutes in Hyderabad through administering Attitudes toward Disabled Persons Scale – Form O and Behavioural Assessment Scales for Indian Children with Mental Retardation (Part-B). On statistical analysis, parental attitudetowards disability as predictor and the behavioural problem of children as criterion indicated a significant result (R2= 0.11, β= -0.33, F= 6.10, p= 0.017). Findings reveal that children with intellectual disability are less prone to behavioural problems if the parents have an attitude that their chid with intellectual disability is not different from other "normal" children. It gives insight upon the necessity to focus upon parental attitude towards disability in order to bring about changes in behaviour problems among children with intellectual disability